Exploring the experiences of operating room nurses on the infection prevention and control programme at Intermediate Hospital, Katutura, Windhoek, Namibia. - hortensia Kamati; Dr. Teopolina Enkono (Student's Journal of Health Research Africa, 2026)
Background Infection Prevention and Control (IPC) is essential for protecting patients and healthcare workers from healthcare-associated infections (HAIs), particularly in operating rooms where invasive procedures and exposure to biological materials increase infection risks. Operating room nurses play a central role in implementing IPC measures. However, effective implementation may be influenced by availability of resources, staffing, workload, training, supervision, and institutional support. This study explored the experiences of operating room nurses regarding the implementation of the IPC programme at Intermediate Hospital Katutura (IHK), Windhoek, Namibia. Methods A qualitative exploratory design was employed. Ten operating room nurses were purposively selected based on predefined eligibility criteria, including a minimum of two years of operating-room experience. Data were collected through face-to-face semi-structured interviews using an interview guide. Interviews were audio-recorded with participants' consent, transcribed verbatim, and analysed thematically using Braun and Clarke's six-phase approach, with support from MAXQDA version 24. Results Three major themes emerged: experiences with IPC programme implementation, challenges in adhering to IPC measures, and facilitators of effective IPC implementation. Participants demonstrated knowledge of IPC practices, including hand hygiene, use of personal protective equipment, sterilisation, environmental cleaning, and waste management. However, implementation was constrained by shortages of PPE and other supplies, staffing shortages, high workloads, emergency procedures, limited refresher training, and inadequate supervision. Facilitators included accessible IPC guidelines, teamwork and peer support, supportive leadership, supervision, and continuous professional development. Conclusion Operating room nurses understood the importance of IPC and demonstrated commitment to infection prevention practices. Nevertheless, organisational and resource-related barriers affected consistent implementation. Recommendation Hospital management and the Ministry of Health and Social Services should strengthen IPC resource availability, staffing, continuous professional development, supportive supervision, monitoring, and feedback mechanisms to promote sustained compliance and patient safety.